2022
DOI: 10.54322/kairaranga.v23i1.281
|View full text |Cite
|
Sign up to set email alerts
|

The beauty of universal design for learning (UDL) and why everyone in early childhood education and intervention should be using it

Abstract: This article seeks to highlight the importance of consciously implementing universal design for learning principles in practice in early childhood intervention. Universal design for learning (UDL) is based on three principles: 1) providing multiple means of engagement, 2) providing multiple means of representation, and 3) providing multiple means of action and expression. The term UDL is being championed in New Zealand schools but there are few examples of how early childhood settings and early childhood kaiak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Overall, the data showed that a large majority of participants used some principles from the Universal Design for Learning framework, although they were not always aware of what they were doing, or even perhaps making conscious decisions to implement them (Moffat, 2022). Participants primarily taught juniors (Year 1-4), although senior teachers were represented (Year 5-8).…”
Section: Understanding Udl As a Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the data showed that a large majority of participants used some principles from the Universal Design for Learning framework, although they were not always aware of what they were doing, or even perhaps making conscious decisions to implement them (Moffat, 2022). Participants primarily taught juniors (Year 1-4), although senior teachers were represented (Year 5-8).…”
Section: Understanding Udl As a Frameworkmentioning
confidence: 99%
“…Many of these strategies are strong factors within New Zealand schools, such as ensuring programmes are culturally responsive for learners. Overall, New Zealand teachers create safe environments for their learners, but more intentional thought needs to be put into ensuring this is true for all autistic learners (Education Review Office, 2022; Moffat, 2022).…”
Section: Conclusion With Recommendations For Future Actionmentioning
confidence: 99%
“…The UDL approach is based on three fundamental principles, which aim to provide diverse means of engagement, representation, and action and expression (Griful-Freixenet et al, 2021;Lin & Barber, 2022;Moffat, 2022). Engagement in UDL involves helping learners find their purpose, stay motivated, and develop an interest in the learning process (Boothe et al, 2018).…”
Section: Universal Design For Learning (Udl)mentioning
confidence: 99%